CLAMP regulates zygotic genome activation in Drosophila embryos. Issue 2 (9th August 2021) - Colonnetta, Megan M; Abrahante, Juan E; Schedl, Paul; Gohl, Daryl M; Deshpande, Girish
Abstract: Embryonic patterning is critically dependent on zygotic genome activation (ZGA). In Drosophila melanogaster embryos, the pioneer factor Zelda directs ZGA, possibly in conjunction with other factors. Here, we have explored the novel involvement of Chromatin-Linked Adapter for MSL Proteins (CLAMP) during ZGA. CLAMP binds thousands of sites genome-wide throughout early embryogenesis. Interestingly, CLAMP relocates to target promoter sequences across the genome when ZGA is initiated. Although there is a considerable overlap between CLAMP and Zelda binding sites, the proteins display distinct temporal dynamics. To assess whether CLAMP occupancy affects gene expression, we analyzed transcriptomes of embryos zygotically compromised for either clamp or zelda and found that transcript levels of many zygotically activated genes are similarly affected. Importantly, compromising either clamp or zelda disrupted the expression of critical segmentation and sex determination genes bound by CLAMP (and Zelda). Furthermore, clamp knockdown embryos recapitulate other phenotypes observed in Zelda-depleted embryos, including nuclear division defects, centrosome aberrations, and a disorganized actomyosin network. Based on these data, we propose that CLAMP acts in concert with Zelda to regulate early zygotic transcription.